The Zonation of Abration Speed Characteristics and its Handling Technique of Jalinbar of North Bengkulu as Vital Band Transportation - Suwarsono, Suwarsono; Supiyati, Supiyati; Suwardi, Suwardi (UI Scholars Hub, 2011)
The Zonation of Abration Speed Characteristics and its Handling Technique of Jalinbar of North Bengkulu as Vital Band Transportation. Jalinbar Bengkulu is a vital infrastructure for traffic service, goods, agriculture products, mining, plantation and oils distribution. Abration due to scour of seawater often make these roads jammed and discrupts the peoples economy movement. The aims of this research was to investigate the abration speed of all segment of Jalinbar. The research method was a combination of two methods: A determination of swash energy of sea water using photometer and determination of rocks binding energy using douche method. The result shows that the maximum abration speed was in north area of Bengkulu beach, occurred in Air Dikit I, Urai I, and Urai II. The abration speed was 2-2,5 m/year. The other abration speed occurred in Air Petai, Palik, Pekik Nyaring in 0,5-1 m/year. On the other hand, Pasar Ketahun, Selolong, Air Serangai I, Air Serangai II, Kota Agung, Ulu Danau and Harapan was 1-2 m/year. The handling technique of all abration location of Jalinbar Bengkulu, north area using groin and jetty, except for Air Dikit and Urai I using jetty. Beside that, the handling technique for Air Serangai II using a combination of groin, jetty, and gabions.